A single-atom material with precise coordination of tripyrrole-N and its preparation method and application in fuel cells

By using tripyrrole-N precisely coordinated single-atom materials in H2O2-based fuel cells, the problem of insufficient activity and stability of existing catalysts is solved, and efficient and stable electrocatalytic performance is achieved, which is suitable for industrial applications.

CN118299594BActive Publication Date: 2025-02-11TIANJIN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410393628.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-02
Publication Date
2025-02-11
Estimated Expiration
2044-04-02

AI Technical Summary

Technical Problem

The existing H2O2-based fuel cell cathode catalysts have problems with low Pt utilization and low reactivity, and the synthesis of M-N-C materials cannot achieve uniform and controllable synthesis of a single nitrogen configuration, resulting in poor performance in fuel cell applications.

Method used

Using single-atom materials with precise coordination of tripyrrole-N, carbon nanotubes and twisted wrinkled polypyrrole nanosheets are used as substrates and coordination environments, and Zn atoms and N atoms of tripyrrole are used to accurately coordinate to form defect-free Metal active site.

Benefits of technology

It achieves high reactivity, selectivity and stability, improves the efficiency and stability of fuel cells, and has simple preparation methods and easy materials, which are suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118299594B_ABST
    Figure CN118299594B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fuel cells, in particular to a single-atom material with tripyrrole-N precise coordination, a preparation method thereof and an application in a fuel cell. The single-atom material comprises: a disordered nitrogen-containing carbon substrate and Zn atoms uniformly dispersed in a single-atom form and loaded on the disordered nitrogen-containing carbon substrate. The disordered nitrogen-containing carbon substrate comprises carbon nanotubes and twisted and wrinkled polypyrrole nanosheets. Zn is introduced as a doping element into the polypyrrole to obtain a tripyrrole-N coordinated Zn site. The single-atom material has abundant metal active centers with no defects nearby, and thus has good electrochemical catalytic activity, selectivity and stability, can be used for cathode catalysis of H2O2-based fuel cells, and can also be used for preparing hydrogen peroxide by electrocatalytic oxygen reduction. The device required for the preparation is simple, the materials are readily available and inexpensive, the preparation method is easy to implement, and the material is suitable for industrial promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fuel cells, in particular to a single-atom material with precise coordination of tripyrrole-N and a preparation method thereof and application in fuel cells. Background Art

[0002] H2O2-based fuel cells are a special type of fuel cell that uses liquid or gaseous hydrogen peroxide (H2O2) and air (oxygen) as reaction materials to generate electricity through a specific electrochemical reaction, while only generating a small amount of heat. It has the advantages of high energy density, stable discharge voltage, long storage life, high safety factor, and no ecological pollution, and is regarded as a potential new energy vehicle power source. In the prior art, the cathode catalysts commonly used in H2O2-based fuel cells mainly include Pt catalysts, low Pt catalysts, and non-Pt catalysts. Although Pt catalysts have the highest reaction activity, they are expensive; low Pt catalysts use carbon black as carriers, etc., and although they can reduce the Pt content while maintaining a high reaction activity, there is a problem that Pt particles can easily enter the micropores on the surface of the carrier, resulting in a low Pt utilization rate. Therefore, the research and development of non-Pt catalysts with high reaction activity, good selectivity, and good stability is of great significance to improving the efficiency and stability of fuel cells.

[0003] In recent years, metal nitrogen-doped carbon (MNC) materials with clear active centers have attracted widespread attention due to their particularly high activity and selectivity in various chemical reactions, and have application prospects in H2O2-based fuel cell cathode catalysts. At present, the synthesis of MNC materials can only increase the proportion of the target configuration to a certain extent, and cannot achieve uniform and controllable synthesis of a single nitrogen configuration. Moreover, most MNC materials synthesized by high-temperature carbonization have defects on the surface. Experimental and computational studies have shown that the presence of these defects will also affect the ORR performance of MNC materials (Advanced Science News, 2023, 10, 2305194), resulting in low reaction activity when used as H2O2-based fuel cell cathode catalysts.

[0004] In order to solve the above problems, researchers use metal macromolecules such as porphyrin and phthalocyanine with clear pyrrole-N structure as ORR catalysts. In order to improve the dispersibility, conductivity and stability of metal macromolecules, metal macromolecules such as porphyrin and phthalocyanine are usually loaded onto carbon tubes or functionalized carbon tubes by π-π stacking. However, it has been found that the phthalocyanine molecules attached to carbon tubes have chemical instability in actual reaction environments (Nature Energy, 2016, 1, 16130). In addition, there are problems such as changes in the catalytic activity of metal active sites and the inability to accurately control the position of functional groups on carbon tubes when functionalized carbon tubes are combined with metal macrocycles.

[0005] Therefore, it is of great significance to synthesize fuel cell cathode catalytic materials with no defects near the metal active sites using substrates that have precise coordination with metal atoms. Summary of the invention

[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a single-atom material with precise coordination of tripyrrole-N and a preparation method thereof and application in a fuel cell.

[0007] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0008] First, the present invention proposes a single-atom material with precise tripyrrole-N coordination, comprising: a disordered nitrogen-containing carbon substrate and Zn atoms uniformly dispersed in the form of single atoms and loaded on the disordered nitrogen-containing carbon substrate, wherein the disordered nitrogen-containing carbon substrate comprises carbon nanotubes and twisted and wrinkled polypyrrole nanosheets, and Zn is introduced into polypyrrole as a doping element to obtain a tripyrrole-N coordinated Zn site.

[0009] Mechanism: This single-atom material uses carbon nanotubes as conductive agents and substrate templates, and polypyrrole nanosheets as coordination environments. The polypyrrole nanosheets are disordered. Since the N atoms inside them contain lone pairs of electrons, the three pyrrole N atoms are precisely coordinated with the Zn atoms, so that the Zn element is introduced into the polypyrrole as a doping element to obtain a tripyrrole-N coordinated Zn site, which then has both good electrocatalytic performance and high conductivity, enabling it to have excellent reactivity, selectivity, and stability in the electrocatalytic two-electron oxygen reduction reaction, and ultimately achieve a high yield.

[0010] Preferably, through ICP testing, the content of Zn element is 2.8-4wt%, preferably 3.0-3.4wt%, most preferably 3.2wt%.

[0011] The present invention unexpectedly found that when the content of Zn element in the single-atom material is 2.8-4wt%, when it is used as an ORR catalyst, Zn and 2e - The interaction between the intermediates (*OOH) of the -ORR is moderate, the number of electrons transferred from Zn to O in *OOH is moderate, and the resulting single-atom material 2e - -ORR catalytic activity is high. When the content of Zn element is 3.0-3.4wt%, the catalytic activity is higher. When the content of Zn element is 3.2wt%, the catalytic activity is the highest.

[0012] Second, the present invention provides a method for preparing the above-mentioned tripyrrole-N precisely coordinated single-atom material, comprising the following steps:

[0013] S1, dissolving and uniformly dispersing carbon nanotubes and pyrrole monomers in a solvent to obtain a precursor;

[0014] S2, adding an oxidant and a Zn salt to the precursor, stirring at a constant temperature, the pyrrole monomer undergoes a polymerization reaction under the action of the oxidant to generate twisted and wrinkled polypyrrole, and Zn is precisely coordinated with N having a lone pair of electrons in the polypyrrole;

[0015] S3, filtering and washing the product obtained in S2, and then drying and grinding.

[0016] The present invention uses carbon nanotubes as conductive agents and substrate templates and twisted and wrinkled polypyrrole as a coordination environment, which not only achieves the precise regulation of the coordination single-atom environment, but also ensures the high conductivity of the single-atom material, giving it excellent electrocatalytic performance.

[0017] Preferably, in S1, the carbon nanotubes have a tube length of 15-30 μm and a tube diameter of 3-15 nm, the solvent is water, and the mass ratio of the carbon nanotubes to the pyrrole monomer is 1:(5-15).

[0018] In this embodiment, considering the conductivity of the single-atom material and the coordination environment of the Zn atom, the mass ratio of the carbon nanotube to the pyrrole monomer in water is 1:(5-15), and the preferred mass ratio is 1:6.5. Within this mass ratio range, the pyrrole monomer can be polymerized to generate an appropriate amount of disordered polypyrrole, and an appropriate amount of disordered polypyrrole can be uniformly and stably wrapped on the surface of the carbon nanotube, which not only makes the single-atom material exhibit stable electrochemical properties in practical applications, but also provides a suitable coordination environment for Zn.

[0019] In this embodiment, considering that filtration is required later, in order not to affect the preparation efficiency, the amount of solvent used should not be too much, as long as it can disperse the pyrrole and carbon nanotubes relatively evenly.

[0020] In this embodiment, the specific dispersion method is not limited, and any existing dispersion means can be used, such as manual stirring, magnetic stirring, ultrasound, etc. Various dispersion means can be used alone or in combination, and preferably ultrasound and magnetic stirring are combined.

[0021] Preferably, in S2: the oxidant is an aqueous solution of hydrogen peroxide with a mass percentage of 25-35%, the Zn salt is anhydrous zinc acetate or anhydrous zinc nitrate, with anhydrous zinc acetate being preferred, the volume ratio of the oxidant to the pyrrole monomer is 1:(0.36-1.46), the molar ratio of the pyrrole monomer to the anhydrous zinc acetate is (1-10):1, and the constant temperature stirring is specifically carried out by constant temperature water bath stirring, the water bath temperature is 4-40°C, preferably 25-35°C, and the stirring time is 4-12h.

[0022] In this embodiment, the mass fraction of the aqueous solution of hydrogen peroxide and the water bath temperature have a significant effect on the generation of polypyrrole. The mass fraction of the aqueous solution of hydrogen peroxide and the water bath temperature should not be too high or too low. Too high will cause the polymerization of pyrrole monomer to generate polypyrrole too fast and the chain length of polypyrrole to be too short, which will then make the polypyrrole branch more and more, the conductivity is getting worse and worse, and the Zn metal sites coordinated by the catalytic tripyrrole become fewer and fewer; too low will not generate polypyrrole. The present invention has found through creative labor that when the mass percentage of the aqueous solution of hydrogen peroxide is 25-35% and the water bath temperature is 4-40°C, the chain length of the obtained polypyrrole is moderate, which can maintain good conductivity and realize more Zn active sites, and there are no defects near the Zn active sites. Among them, the mass percentage of the aqueous solution of hydrogen peroxide is preferably 30%, the water bath temperature is preferably 25-35°C, and 30°C is most preferred. The specific operation of constant temperature stirring is preferably stirred at 30°C for 8h. In addition, using the aqueous solution of hydrogen peroxide with the above mass percentage as the oxidant is only a preferred technical solution, and is not intended to limit the oxidant to only hydrogen peroxide. Other types of oxidants that do not introduce impurities into the system may also be used.

[0023] In this embodiment, when the volume ratio of the oxidant to the pyrrole monomer is 1:(0.36-1.46) and the molar ratio of the pyrrole monomer to the anhydrous zinc acetate is (1-10):1, the content of Zn element in the obtained monomer material is 2.8-4wt%. When the preferred volume ratio of the oxidant to the pyrrole monomer is 1:0.73 and the molar ratio of the pyrrole monomer to the anhydrous zinc acetate is 3:1, the content of Zn element in the obtained monomer material is 3.2wt%, and the single-atom material obtained under this condition has the highest activity.

[0024] Preferably, in S3, the washing is performed by washing with deionized water, and the drying is performed by vacuum drying at 30-60° C. for at least 12 hours.

[0025] In this embodiment, the drying temperature should not be lower than 30°C, otherwise it will take a long time to dry, affecting the preparation efficiency; the drying temperature should not be higher than 60°C, otherwise it may destroy the structure of the single-atom material, thereby affecting its electrocatalytic performance. The preferred drying temperature is 40°C and the drying time is 24h.

[0026] In this embodiment, vacuum drying is only used as a preferred technical solution and is not used to limit the drying method to vacuum drying. Other existing drying methods such as freeze drying, spray drying, etc. can be used in the present invention.

[0027] Thirdly, the present invention proposes the application of the above-mentioned tripyrrole-N precisely coordinated single atom material in fuel cells, which can be used as a cathode catalyst for H2O2-based fuel cells.

[0028] Preferably, the specific process is: uniformly dispersing the single-atom material with precise coordination of tripyrrole-N in a mixed solution of nafion, isopropanol and water to obtain a slurry with a concentration of 3-6 mg / mL, taking an appropriate amount of the slurry and drop-coating it on a glassy carbon electrode, and drying it at room temperature to obtain a glassy carbon electrode with the single-atom material with precise coordination of tripyrrole-N loaded on its surface; using 0.1M KOH aqueous solution as electrolyte, the glassy carbon electrode as working electrode, high-purity carbon rod as counter electrode, and Ag / AgCl as reference electrode, to perform an activity test of H2O2 fuel cell.

[0029] Fourthly, the present invention proposes the application of the above-mentioned tripyrrole-N precisely coordinated single-atom material in the preparation of hydrogen peroxide by electrocatalytic oxygen reduction.

[0030] The specific process is: uniformly dispersing the single-atom material with precise coordination of tripyrrole-N in a mixed solution of nafion, isopropanol and water to obtain a slurry with a concentration of 3-6 mg / mL, taking an appropriate amount of the slurry and drop-coating it on a glassy carbon electrode or hydrophobic carbon paper, and drying it at room temperature to obtain a glassy carbon electrode or hydrophobic carbon paper with the single-atom material with precise coordination of tripyrrole-N loaded on the surface; using 0.1M KOH aqueous solution as electrolyte, the glassy carbon electrode or hydrophobic carbon paper as working electrode, high-purity carbon rod as counter electrode, and Ag / AgCl as reference electrode, electrocatalytic oxygen reduction to prepare hydrogen peroxide.

[0031] In this embodiment, when preparing hydrogen peroxide by electrocatalytic oxygen reduction, hydrophobic carbon paper is preferably used for experiments on hydrogen peroxide yield and stability, and a glassy carbon electrode, especially a rotating glassy carbon disk ring electrode, is preferably used for experiments on hydrogen peroxide selectivity.

[0032] Furthermore, when it is used for electrocatalytic oxygen reduction to prepare hydrogen peroxide, the average growth rate of H2O2 concentration can reach 494.9 mg / L·h. Compared with existing non-metallic catalysts, monometallic catalysts and bimetallic catalysts, the tripyrrole-N precisely coordinated single-atom material proposed in the present invention has a higher yield for electrocatalytic oxygen reduction to prepare hydrogen peroxide, and is a relatively green catalyst, which can be used for economical, efficient and small-scale preparation of hydrogen peroxide.

[0033] Compared with the prior art, the present invention obtains a single-atom material of tripyrrole-N precise coordination which is abundant in number and has no defects near the metal active center by precisely coordinating the three pyrrole N atoms with the Zn atoms. The Zn site has good electrochemical catalytic activity, selectivity and stability, and can be used for cathode catalysis of H2O2-based fuel cells and for preparing hydrogen peroxide by electrocatalytic oxygen reduction. Moreover, the device required for the preparation is simple, the materials are readily available and inexpensive, and the preparation method is easy to implement, which is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 The structural diagram of the single-atom material with precise coordination of tripyrrole-N proposed in the present invention;

[0036] Figure 2 This is the SEM image of ppy-ZnN3-3 obtained in Example 1;

[0037] Figure 3 TEM image of ppy-ZnN3-3 obtained in Example 1;

[0038] Figure 4 Another TEM image and Mapping element distribution diagram of ppy-ZnN3-3 obtained in Example 1;

[0039] Figure 5 This is the XPS graph of ppy-ZnN3-3 obtained in Example 1;

[0040] Figure 6 : A is the synchrotron radiation pattern of ppy-ZnN3-3 obtained in Example 1, and B is the R space fitting diagram of the synchrotron radiation pattern;

[0041] Figure 7 Cyclic voltammetry curves of the products of Example 1 and Comparative Example 1;

[0042] Figure 8 The linear sweep voltage curve (LSV) of the electrocatalytic oxygen reduction to prepare hydrogen peroxide in Ar and O2 saturated electrolytes at a scan rate of 10 mV / s using the ppy-ZnN3-3 obtained in Example 1 as a catalyst;

[0043] Fig. 9 The linear sweep voltage curve (LSV) of the electrocatalytic oxygen reduction to produce hydrogen peroxide in a 0.10M KOH aqueous solution containing 50mM hydrogen peroxide using the ppy-ZnN3-3 obtained in Example 1 as a catalyst;

[0044] Fig.10 The amperometric curve and the change graph of hydrogen peroxide concentration when the ppy-ZnN3-3 obtained in Example 1 is used as a catalyst to prepare hydrogen peroxide by electrocatalytic oxygen reduction in a 0.10M KOH aqueous solution containing 50mM hydrogen peroxide for 48 hours;

[0045] Fig.11 Cyclic voltammetry curves of the products of Example 1, Example 6-Example 8;

[0046] Fig.12 The linear sweep voltage curve (LSV) of the electrocatalytic oxygen reduction to prepare hydrogen peroxide using the products of Example 1, Example 6, and Example 7 as catalysts at a scan rate of 5 mV / s and an O2-saturated electrolyte;

[0047] Fig.13 The selectivity curves for preparing hydrogen peroxide using the products of Example 1, Example 6, and Example 7 as catalysts;

[0048] Fig.14 TEM image of ppy-CuN3-3 obtained in Comparative Example 1;

[0049] Fig.15 TEM image of ppy-CoN3-3 obtained in Comparative Example 2;

[0050] Fig.16 Graphs showing the selectivity of hydrogen peroxide using the products of Example 1, Comparative Example 1 and Comparative Example 2 as catalysts, respectively;

[0051] Fig.17 Graphs showing the selectivity of hydrogen peroxide using the products of Examples 1 to 4 as catalysts, respectively;

[0052] Fig.18 The graphs are hydrogen peroxide selectivities using the products of Example 1 and Example 5 as catalysts, respectively. DETAILED DESCRIPTION

[0053] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0054] In the following examples and comparative examples, carbon nanotubes were purchased from Kaisa (Guangdong) New Materials Co., Ltd. Model: multi-walled carbon nanotubes, crystal system: hexagonal system, specific surface area 250-270m 2 / g, tube diameter 3-15nm, tube length 15-30μm; the glassy carbon electrode is a rotating glassy carbon disk ring electrode from PINE, USA, model E7R9.

[0055] Example 1

[0056] A single-atom material with precise coordination of tripyrrole-N is prepared according to the following steps:

[0057] Step 1, add carbon nanotubes, pyrrole and 20 ml of deionized water into a 50 mL beaker, first ultrasonicate for 30 min, then stir on a magnetic stirrer for 30 min to obtain a precursor, wherein the mass ratio of carbon nanotubes to pyrrole is 1:6.5;

[0058] Step 2, adding 30% by mass of aqueous hydrogen peroxide solution and anhydrous zinc acetate to the above precursor, and stirring at a constant temperature of 30° C. in a water bath for 8 hours to obtain a mixture, wherein: the volume ratio of the aqueous hydrogen peroxide solution to pyrrole is 1:0.73, and the molar ratio of pyrrole to anhydrous zinc acetate is 3:1;

[0059] Step 3, the mixture obtained in step 2 is filtered, washed with deionized water, vacuum dried at 40°C for 24 hours, and ground to obtain a single-atom material with precise coordination of tripyrrole-N, marked as ppy-ZnN3-3.

[0060] The structural diagram of the product obtained in Example 1 is as follows Figure 1 As shown in the figure: the three pyrrole N atoms are precisely coordinated with the Zn atoms, the pyrrole monomers are polymerized to form disordered polypyrrole, and the Zn element is introduced into the polypyrrole as a doping element to form a tripyrrole-N coordinated Zn site. Figure 2-Figure 3 As shown in the figure, the morphology of the product obtained in Example 1 was observed by SEM and TEM. Under the action of aqueous hydrogen peroxide solution, the polypyrrole with high disorder was obtained by constant temperature stirring at 30°C for 8 hours. The polypyrrole was in a twisted and wrinkled shape and was uniformly loaded on the carbon nanotubes. Figure 4 As shown in the figure: By performing a Mapping element distribution test on the product obtained in Example 1, it can be seen that the four elements of C, N, O, and Zn are evenly distributed, indicating the successful synthesis of polypyrrole and the successful introduction of metal Zn; the ICP test shows that the content of Zn element is 3.2wt%. Further, the structure is characterized by X-ray photoelectron spectroscopy (XPS) and synchrotron radiation absorption spectroscopy (XAFS), as shown in the figure. Figure 5 and Figure 6 As shown in Figure A: There is an obvious Zn-N bond in the N1s fine spectrum of the XPS spectrum and the R space spectrum of the XAFS spectrum, and there is no characteristic peak of the Zn-O bond, indicating that Zn is bonded to N and achieves precise coordination of Zn-N, such as Figure 6 As shown in Figure B, the synchrotron radiation absorption spectrum and its R-space fitting diagram have a high degree of match, which shows that the obtained single-atom material has precise tripyrrole-N precise coordination, combined with Figure 3 and Figure 6 It can be seen that there are no defects near the Zn active sites.

[0061] The ppy-ZnN3-3 obtained in Example 1 is uniformly dispersed in a mixed solution of anion, isopropanol and water, with a volume ratio of nafion, isopropanol and water being 20:180:800, to obtain a slurry with a concentration of 4 mg / mL. An appropriate amount of the slurry is taken and drop-coated on a glassy carbon electrode, and then dried at room temperature to obtain a glassy carbon electrode with a single-atom material with tripyrrole-N precisely coordinated on its surface. The glassy carbon electrode is used as a working electrode, a high-purity carbon rod is used as a counter electrode, and Ag / AgCl (RHE) is used as a reference electrode. In a 0.1 M KOH aqueous solution, a linear polarization curve is measured at room temperature, as shown in detail. Figure 7 As shown: Compared with the glassy carbon electrode without ppy-ZnN3-3 (blank control), the ppy-ZnN3-3 loaded electrode has stronger electrochemical activity and can be used for cathode catalysis in H2O2-based fuel cells.

[0062] The ppy-ZnN3-3 obtained in Example 1 was uniformly dispersed in a mixed solution of nafion, isopropanol and water, the volume ratio of nafion, isopropanol and water being 20:180:800, to obtain a slurry with a concentration of 5 mg / mL, an appropriate amount of the slurry was taken and drop-coated on a commercial hydrophobic carbon paper electrode, and dried at room temperature to obtain a hydrophobic carbon paper with ppy-ZnN3-3 loaded on the surface, the hydrophobic carbon paper was used as the working electrode, Pt as the counter electrode, and Ag / AgCl as the reference electrode, and the yield and stability of the electrocatalytic oxygen reduction to prepare hydrogen peroxide were determined.

[0063] like Figure 8 As shown in the figure: In the O2-saturated electrolyte, ppy-ZnN3-3 showed an obvious ORR current at the starting reaction potential of 0.80V vs.RHE, but it did not exist in the Ar-saturated electrolyte, indicating that ppy-ZnN3-3 underwent an ORR reaction and had a high ORR activity. Fig. 9 As shown in the figure: the reaction current of ppy-ZnN3-3 in 0.1M KOH+1mmol H2O2 electrolyte is almost the same as that in Ar environment, indicating that ppy-ZnN3-3 has a very low ability to decompose H2O2 and can ensure long-term accumulation of H2O2. - -ORR stability, such as Fig.10 As shown: the cumulative concentration of H2O2 in the electrolyte was tested every 1 hour, and the average growth rate of H2O2 concentration was measured to be 494.9 mg / L·h. After 48 hours, the cumulative H2O2 concentration reached 23.75 g / L, indicating that the electrocatalytic oxygen reduction preparation of hydrogen peroxide by ppy-ZnN3-3 not only has a high yield but also has good stability.

[0064] Example 2

[0065] Compared with Example 1, the water bath temperature was adjusted from 30°C to 4°C, and the rest were the same as Example 1.

[0066] Example 3

[0067] Compared with Example 1, the water bath temperature was adjusted from 30°C to 20°C, and the rest was the same as Example 1.

[0068] Example 4

[0069] Compared with Example 1, the water bath temperature was adjusted from 30°C to 40°C, and the rest was the same as Example 1.

[0070] Example 5

[0071] Compared with Example 1, anhydrous zinc acetate was replaced with anhydrous zinc nitrate of the same amount, and the rest was the same as Example 1. According to ICP test, the content of Zn element in the product was 3.0wt%.

[0072] like Fig.18 As shown: when anhydrous zinc nitrate (Example 5) is selected as the Zn salt, the selectivity of preparing hydrogen peroxide by electrocatalytic oxygen reduction using the obtained product as a catalyst is 65%, and when anhydrous zinc acetate (Example 1) is selected as the Zn salt, the selectivity of preparing hydrogen peroxide by electrocatalytic oxygen reduction using the obtained product as a catalyst is 90%, and the Zn salt is preferably anhydrous zinc acetate. Moreover, the content of Zn element in the product is lower than that in Example 1. Therefore, we speculate that when anhydrous zinc nitrate is selected as the zinc salt, under the specific environment defined by the preparation method, zinc nitrate may be partially oxidized by hydrogen peroxide to generate zinc oxide, resulting in insufficient number of Zn atoms coordinated with pyrrole N, making the actual generation amount of active sites less than the theoretical generation amount, resulting in a decrease in the content of Zn element. The reduction in the number of active sites makes it unable to effectively play a catalytic role.

[0073] Example 6

[0074] Compared with Example 1, the molar ratio of pyrrole to anhydrous zinc acetate was adjusted from 3:1 to 1:1, and the rest was the same as Example 1. According to ICP test, the content of Zn element in the product was 3.4wt%.

[0075] Example 7

[0076] Compared with Example 1, the molar ratio of pyrrole to anhydrous zinc acetate was adjusted from 3:1 to 2:1, and the rest was the same as Example 1. According to ICP test, the content of Zn element in the product was 3.3 wt%.

[0077] Example 8

[0078] Compared with Example 1, the molar ratio of pyrrole to anhydrous zinc acetate was adjusted from 3:1 to 10:1, and the rest was the same as Example 1. According to ICP test, the content of Zn element in the product was 2.8wt%.

[0079] When the molar ratio of pyrrole monomer to anhydrous zinc acetate is (1-10):1, a single atom material with highly active tripyrrole-N precisely coordinated can be obtained. The linear polarization curves of the products of Examples 6-8 and the unloaded glassy carbon electrode are measured by the same test method as in Example 1. Fig.11 As shown: When the molar ratio of pyrrole to anhydrous zinc acetate is 1:1, 2:1, 3:1, and 10:1, the electrochemical activity is: Example 1> Example 8> Example 7> Example 6> No load (blank control). In Example 1, the molar ratio of pyrrole to anhydrous zinc acetate is 3:1, which meets the stoichiometric coordination requirements. At this time, the amount of Zn site generated is the largest, and the catalytic activity of the obtained single-atom material is the highest. Furthermore, the present invention also explores the effects of the products obtained at different ratios of pyrrole to anhydrous zinc acetate on the selectivity and activity of hydrogen peroxide. Fig.12 and Fig.13 As shown: When the molar ratio of pyrrole to anhydrous zinc acetate is 3:1, the obtained product is 2e - -ORR has high selectivity and activity, which makes it show high H2O2 activity and selectivity; when the molar ratio of pyrrole to anhydrous zinc acetate is 10:1 and 2:1, the selectivity is close, which shows that the Zn content should not be too high or too low. Too high or too low is not conducive to obtaining higher selectivity.

[0080] Example 9

[0081] Compared with Example 1, the water bath temperature was adjusted from 30°C to 25°C, and the rest was the same as Example 1.

[0082] Example 10

[0083] Compared with Example 1, the water bath temperature was adjusted from 30°C to 35°C, and the rest was the same as Example 1.

[0084] like Fig.17As shown: when the water bath temperature is 4°C (Example 2), 20°C (Example 3), 30°C (Example 1), and 40°C (Example 4), the selectivity of the electrocatalytic oxygen reduction of the obtained product as a catalyst to prepare hydrogen peroxide is 70%, 80%, 90%, and 85% respectively. The selectivity shows a trend of first increasing and then decreasing with the increase of the water bath temperature, reaching the highest at 30°C. Further, the selectivity of the electrocatalytic oxygen reduction of the products obtained in Examples 9 and 10 to prepare hydrogen peroxide was tested by the same method. When the water bath temperature was 25°C, the selectivity was 87%; when the water bath temperature was 35°C, the selectivity was 88%. We analyzed that low temperatures are not conducive to the formation of polypyrrole and the Zn coordination environment is not good. When the temperature is high, the polypyrrole formation rate is too fast, resulting in a shorter polypyrrole chain length, more branches, and poorer conductivity. Through creative experiments, we confirmed that the constant temperature water bath temperature should be 4-40°C, preferably 25-35°C, with 30°C being the best. The polypyrrole generated at this temperature has moderate chain length and branches, and a good Zn coordination environment, which can not only maintain conductivity but also realize the most Zn active sites.

[0085] Embodiment 11

[0086] Compared with Example 1, the mass ratio of carbon nanotubes to pyrrole was adjusted from 1:6.5 to 1:5, and the rest was the same as Example 1.

[0087] Example 12

[0088] Compared with Example 1, the mass ratio of carbon nanotubes to pyrrole was adjusted from 1:6.5 to 1:15, and the rest was the same as Example 1.

[0089] The cyclic voltammetry curves of the products obtained in Examples 11 and 12 were tested by the same test method as in Example 1, showing that they all had good electrochemical activity, but were slightly inferior to that in Example 1. The linear scanning voltage curves of the products obtained in Examples 13 and 14 were tested by the same test method as in Example 1. The results show that the products obtained all have high ORR activity and stability, but are slightly inferior to that in Example 1. Insufficient pyrrole monomer will result in a small amount of polypyrrole generated, and too little polypyrrole cannot form a uniform and stable package for carbon nanotubes, which ultimately leads to unstable electrochemical properties of the product; excessive pyrrole monomer will result in a large amount of polypyrrole generated, and too much polypyrrole may cause the package layer to be too thick and unstable, which is not only not conducive to the uniform doping of Zn, but also affects the stability after Zn doping. The preferred mass ratio of pyrrole to carbon nanotubes is 1: (5-15), within which a suitable amount of disordered polypyrrole can be formed, and polypyrrole can be uniformly and stably wrapped on the surface of carbon nanotubes, optimizing the coordination environment of Zn, and ensuring the structural stability of the product, thereby maintaining good electrochemical stability.

[0090] Example 13

[0091] Compared with Example 1, the volume ratio of the aqueous hydrogen peroxide solution to pyrrole is 1:0.36, and the rest is the same as Example 1.

[0092] Embodiment 14

[0093] Compared with Example 1, the volume ratio of the aqueous hydrogen peroxide solution to pyrrole is 1:1.46, and the rest is the same as Example 1.

[0094] The cyclic voltammetry curves of the products obtained in Example 11 and Example 12 were tested by the same test method as in Example 1, showing that they all had good electrochemical activity, but were slightly inferior to that in Example 1. The linear scanning voltage curves of the products obtained in Example 13 and Example 14 were tested by the same test method as in Example 1. The results show that the obtained products all have high ORR activity and stability, but are slightly inferior to that in Example 1. Insufficient use of aqueous hydrogen peroxide solution is not conducive to the production of polypyrrole, and excessive use of aqueous hydrogen peroxide solution will cause excessive distortion and wrinkling of the polypyrrole surface and affect the structural stability of the product. The present invention has been proved through creative labor that the volume ratio of aqueous hydrogen peroxide solution to pyrrole monomer is preferably 1: (0.36-1.46).

[0095] It should be noted that: except for Example 1, the present application also carried out SEM, TEM, Mapping, XPS and XAFS characterization on the remaining examples, and the characterization results were close to those of Example 1. The above examples can all produce single-atom materials with defect-free tripyrrole-N precise coordination near the Zn active site.

[0096] Comparative Example 1

[0097] Compared with Example 1, anhydrous zinc acetate is replaced by copper acetate monohydrate, and the amount of Cu is equal to the amount of Zn. The final product is marked as ppy-CuN3-3.

[0098] The product ppy-CuN3-3 obtained in Comparative Example 1 and the unloaded glassy carbon electrode were tested for linear polarization curves in the same manner as in Example 1. The test results are shown in FIG. Figure 7 As shown in the figure, it can be seen that the loaded ppy-ZnN3-3 has stronger electrochemical activity than the loaded ppy-CuN3-3 and no load. When the metal center is Zn, the obtained Zn site has good H2O2-based fuel cell cathode catalytic activity.

[0099] Comparative Example 2

[0100] Compared with Example 1, anhydrous zinc acetate is replaced by cobalt acetate tetrahydrate, and the amount of Co is equal to the amount of Zn. The final product is marked as ppy-CoN3-3.

[0101] like Fig.14 and Fig.15 As shown in the figure, the morphology of the products obtained in Comparative Examples 1 and 2 is basically consistent with that of the product obtained in Example 1, and the twisted and wrinkled polypyrrole is uniformly loaded on the carbon nanotubes. Fig.16 As shown: The selectivity of preparing hydrogen peroxide by electrocatalytic oxygen reduction using the products obtained in Example 1, Comparative Example 1, and Comparative Example 2 as catalysts is 90%, 53%, and 55% respectively. When the metal center is Zn, the selectivity of the obtained single-atom material is much greater than that of the metal center is Cu and Co. The reason should be: 2e - The interaction between the intermediates (*OOH) of the -ORR is moderate, the number of electrons transferred from Zn to O in *OOH is moderate, and the resulting single-atom material 2e - -High ORR catalytic activity.

[0102] Comparative Example 3

[0103] Compared with Example 1, the molar ratio of pyrrole to anhydrous zinc acetate was adjusted from 3:1 to 0.2:1, and the rest was the same as Example 1.

[0104] Comparative Example 4

[0105] Compared with Example 1, the molar ratio of pyrrole to anhydrous zinc acetate was adjusted from 3:1 to 15:1, and the rest was the same as Example 1.

[0106] The yield of the products obtained in Comparative Examples 3 and 4 when used to prepare hydrogen peroxide was tested in the same test method as in Example 1. The results showed that the average growth rates of the H2O2 concentrations in Comparative Examples 3 and 4 were 230 mg / L·h and 305 mg / L·h, respectively, which were much lower than the yield of Example 1.

[0107] Comparative Example 5

[0108] Compared with Example 1, the water bath temperature was adjusted from 30°C to 1°C, and the rest was the same as Example 1.

[0109] Comparative Example 6

[0110] Compared with Example 1, the water bath temperature was adjusted from 30°C to 50°C, and the rest was the same as Example 1.

[0111] The yield of the products obtained in Comparative Examples 5 and 6 when used to prepare hydrogen peroxide was tested in the same test method as in Example 1. The results showed that the average growth rates of the H2O2 concentrations in Comparative Examples 3 and 4 were 245 mg / L·h and 168 mg / L·h, respectively, which were much lower than the yield of Example 1.

[0112] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Those skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A method for preparing a single-atom material with precise coordination of tripyrrole-N, characterized in that: The steps are as follows: S1, dissolving and uniformly dispersing carbon nanotubes and pyrrole monomers in a solvent to obtain a precursor, wherein the carbon nanotubes have a tube length of 15-30 μm and a tube diameter of 3-15 nm, the solvent is water, and the mass ratio of the carbon nanotubes to the pyrrole monomers is 1:(5-15); S2. Add an oxidant and a Zn salt to the precursor and stir at a constant temperature. The oxidant is an aqueous solution of hydrogen peroxide with a mass percentage of 25-35%, and the Zn salt is anhydrous zinc acetate. The volume ratio of the oxidant to the pyrrole monomer is 1:(0.36-1.46), and the molar ratio of the pyrrole monomer to the anhydrous zinc acetate is (1-10):

1. The constant temperature stirring is specifically carried out by stirring in a constant temperature water bath, the water bath temperature is 25-35°C, and the stirring time is 4-12h. S3, filtering and washing the product obtained in S2, and then drying and grinding.

2. The method for preparing the tripyrrole-N precisely coordinated single-atom material according to claim 1, characterized in that: In S3, the washing is performed by washing with deionized water, and the drying is performed by vacuum drying at 30-60° C. for at least 12 hours.

3. A single-atom material with precise coordination of tripyrrole-N prepared according to the preparation method of claim 1 or 2, characterized in that: include: A disordered nitrogen-containing carbon substrate and Zn atoms uniformly dispersed in the form of single atoms and loaded on the disordered nitrogen-containing carbon substrate. The disordered nitrogen-containing carbon substrate includes carbon nanotubes and twisted and wrinkled polypyrrole nanosheets. Zn is introduced into the polypyrrole as a doping element to obtain a tripyrrole-N coordinated Zn site. According to ICP testing, the content of the Zn element is 2.8-4wt%.

4. The tripyrrole-N precisely coordinated single atom material according to claim 3, characterized in that: According to ICP test, the content of Zn element is 3.0-3.4wt%.

5. The tripyrrole-N precisely coordinated single atom material according to claim 4, characterized in that: According to ICP test, the content of Zn element is 3.2wt%.

6. Use of the tripyrrole-N precisely coordinated single atom material as claimed in claim 3 in a fuel cell.

7. The use of the tripyrrole-N precisely coordinated single atom material in a fuel cell according to claim 6, characterized in that: It is used as a cathode catalyst in H2O2-based fuel cells. The specific process is: uniformly disperse the single-atom material of tripyrrole-N precisely coordinated in a mixed solution of nafion, isopropanol and water to obtain a slurry with a concentration of 3-6 mg / mL, take an appropriate amount of the slurry and drop it on a glassy carbon electrode, dry it at room temperature, and obtain a glassy carbon electrode with the single-atom material of tripyrrole-N precisely coordinated on the surface; use 0.1M KOH aqueous solution as electrolyte, the glassy carbon electrode as working electrode, high-purity carbon rod as counter electrode, and Ag / AgCl as reference electrode to carry out activity test of H2O2 fuel cell.

8. Use of the tripyrrole-N precisely coordinated single atom material as claimed in claim 3 in preparing hydrogen peroxide by electrocatalytic oxygen reduction.

9. The use of the pyrrole-N precisely coordinated single atom material according to claim 8 in the preparation of hydrogen peroxide by electrocatalytic oxygen reduction, characterized in that: The specific process is: uniformly dispersing the single-atom material with precise coordination of tripyrrole-N in a mixed solution of nafion, isopropanol and water to obtain a slurry with a concentration of 3-6 mg / mL, taking an appropriate amount of the slurry and drop-coating it on a glassy carbon electrode or hydrophobic carbon paper, and drying it at room temperature to obtain a glassy carbon electrode or hydrophobic carbon paper with the single-atom material with precise coordination of tripyrrole-N loaded on the surface; using 0.1M KOH aqueous solution as electrolyte, the glassy carbon electrode or the hydrophobic carbon paper as working electrode, high-purity carbon rod as counter electrode, and Ag / AgCl as reference electrode, electrocatalytic oxygen reduction to prepare hydrogen peroxide.

Citation Information

Patent Citations

  • Preparation method of carbon-supported metal polypyrrole oxygen reduction catalyst

    CN102806106A

  • Preparation method and application of Zn-N-C electrocatalyst for efficiently synthesizing H2O2

    CN114807981A

  • Catalyst and its manufacturing method

    JP2008218041A